Efficacy and safety of anticoagulation in atrial fibrillation patients with intracranial hemorrhage: A systematic review and meta-analysis - Qiang Zhou; Xiang Liu; Xian Yang; Xiao-Hui Huang; Yan-Zi Wu; Ying-Ying Tao; Meng Wei (Frontiers Media S.A., 2023)
Background: The benefits and risks of starting anticoagulation therapy, such as direct oral anticoagulations (DOACs) or warfarin, in atrial fibrillation (AF) patients with a history of intracranial hemorrhage (ICH) remain controversial. We performed a systematic review and meta-analysis to compare the safety and efficacy of starting oral anticoagulation (OAC) and non-oral anticoagulation in these patients.Methods: PubMed, Cochrane Library, and Embase were searched from inception to 01 May 2022 for randomized controlled trials and cohort studies, reporting effectiveness and safety outcomes for anticoagulation therapy in atrial fibrillation patients with intracranial hemorrhage. The Newcastle-Ottawa Scale (NOS) and the Cochrane Collaboration tool were used to evaluate bias risks for all randomized controlled trials (RCTs) and cohort studies. An effects model was applied to calculate adjusted hazard ratios (aHRs) for randomized controlled trials and cohort studies.Results: We analyzed data from two randomized controlled trials (304 patients) and seven Cohort studies (17,477 patients). Compared to non-oral anticoagulation, starting oral anticoagulation therapy reduced the risk of Ischemic Stroke/Systemic Embolism (SE) (aHR: 0.64, 95% CI: 0.55-0.57) and all-cause death (aHR: 0.53, 95% CI: 0.35-0.80) in atrial fibrillation patients and a prior history intracranial hemorrhage. Starting oral anticoagulation therapy did not increase the risk of recurrent intracranial hemorrhage (aHR: 1.07, 95% CI: 0.66-1.74), but increased the risk of major bleeding (aHR: 1.38, 95% CI: 1.00-1.91) than no oral anticoagulation therapy. The DOACs had a lower risk of Ischemic Stroke/SE (aHR: 0.84, 95% CI: 0.70-1.00), recurrent intracranial hemorrhage (aHR: 0.63, 95% CI: 0.49-0.82), and all-cause death (aHR: 0.65, 95% CI: 0.48-0.88) compared to warfarin. According to subgroup analyses, starting oral anticoagulation therapy have a higher risk of recurrent intracranial hemorrhage than non-oral anticoagulation therapy (aHR: 1.57, 95% CI: 1.36-1.81) for Asians.Conclusion: After intracranial hemorrhage in atrial fibrillation patients, restarting or initiating oral anticoagulation therapy decreased the risk of Ischemic Stroke/SE and all-cause death but did not increase the risk for recurrent intracranial hemorrhage. Direct oral anticoagulations have better efficacy and safety than warfarin if oral anticoagulation therapy is started. However, starting oral anticoagulation increases the risk for recurrent intracranial hemorrhage in the Asian region.